Lifelong Sports through the Lens of Physical Literacy: Understanding Definitions, Benefits, and Challenges - Wisnu Mahardika; Pinton Setya Mustafa; Luthfie Lufthansa; Tama Anugrah; Sabda Hussain As Shafi (Edumaspul: Jurnal Pendidikan, 2024)
The participation in lifelong sports often encounters obstacles such as lack of individual motivation, inadequate knowledge and skills, as well as unsupportive environment. This article aims to address these issues by discussing the concept of physical literacy as a tool to promote participation in lifelong sports. library research method was used to understand the definition and importance of physical literacy, motor skills development, and the influence of self-confidence, motivation, and competence on participation in physical activities. The results of the library research show that physical literacy is an essential element that encourages individuals to participate in lifelong sports. This includes the knowledge, skills, and attitudes needed to lead an active lifestyle. Understanding the long-term health benefits of physical activity can also be a strong driver for individuals to lead an active lifestyle. The conclusion is that effective educational strategies or interventions need to be developed and implemented to promote physical literacy and lifelong sports participation. Collaboration with the government and other health organizations is crucial to create an environment that supports everyone to participate in physical activities.